Face-work and identities in a discussion about xenophobia - Anyona, Ondigi Evans (University of the Western Cape, 2015)
Magister Artium - MA === International students arriving at the University of the Western Cape (UWC) from other African countries find themselves in a position of having to negotiate their identities and positions with their South African counterparts. The local students too are faced with the prospect of doing the same since they have to coexist with the former. This study aims to investigate how, in a discussion about xenophobia, a selection of UWC students perform face-work and negotiate or construct their identities as well as those of their coparticipants and position themselves in relation to each other. I was interested in exploring how the participants, who were representative of the two groups that clashed in the xenophobic attacks of 2008, would engage with each other while discussing this sensitive topic.The data was gathered during an open-ended discussion among four UWC postgraduate students in a casual, relaxed setting (my room on campus). The transcribed data was then analyzed using a combination of theoretical frameworks from Systemic Functional Linguistics (SFL) and Discourse Analysis. In particular, the SFL theory of modality(Halliday 1994) and Engagement (Martin and White 2005) and Goffman’s (1999[1967]) notion of face were used as tools of analysis.The analysis reveals that participants use a variety of linguistic choices and discourse strategies to maintain face during the discussion of this sensitive topic of xenophobia. The participants make an effort to take care of each other’s face (desires to be appreciated and left free of any imposition) and keep conflicts to a minimum even when they at times disagree and give incriminatory information about each other. It also reveals that the participants, in addition to maintaining face, also construct and negotiate identities which in turn help build in-group solidarity and provide a sense of belonging to them.